Investigation of Migration and Differentiation of Human Mesenchymal Stem Cells on Five‐Layered Collagenous Electrospun Scaffold Mimicking Native Cartilage Structure. Issue 17 (17th May 2016) - Reboredo, Jenny W.; Weigel, Tobias; Steinert, Andre; Rackwitz, Lars; Rudert, Maximilian; Walles, Heike
Abstract : Cartilage degeneration is the major cause of chronic pain, lost mobility, and reduced quality of life for over estimated 150 million osteoarthritis sufferers worldwide. Despite intensive research, none of the available therapies can restore the hyaline cartilage surface beyond just fibrous repair. To overcome these limitations, numerous cell‐based approaches for cartilage repair are being explored that aim to provide an appropriate microenvironment for chondrocyte maintenance and differentiation of multipotent mesenchymal stem cells (MSCs) toward the chondrogenic lineage. Articular cartilage is composed of highly organized collagen network that entails the tissue into four distinct zones and each zone into three different regions based on differences in matrix morphology and biochemistry. Current cartilage implants cannot establish the hierarchical tissue organization that seems critical for normal cartilage function. Therefore, in this study, a structured, multilayered collagen scaffold designed for the replacement of damaged cartilage is presented that allows repopulation by host cells and synthesis of a new natural matrix. By using the electrospinning method, the potential to engineer a scaffold consisting of two different collagen types is obtained. With the developed collagen scaffold, a five‐layered biomaterial is created that has the potency to induce the differentiation of human bone marrow derived MSCs toward the chondrogenic lineage. Abstract : The preparation of a multilayered electrospun scaffold is reported that consists of collagen type I and II and has the potency to induce the differentiation of human mesenchymal stem cells toward the chondrogenic lineage. The novel biomaterial is designed for the replacement of damaged cartilage that allows repopulation by host cells and synthesis of a new natural matrix.